Visual impairment among adults in selected urban area / Nurul Shakira Minhat - Minhat, Nurul Shakira (Faculty of Health Sciences, 2015)
INTRODUCTIONS: The prevalence of visual impairment and the decline of visual function increased with advancing age and become concern to older populations. Visual impairment also reported to be the leading cause of age-related vision disorder. This study was done to determine the prevalence of self-reported visual impairment among adults in urban area. MATERIALS AND METHODS: A self-reported questionnaire was administrated to 40 eligible residents of Shah Alam, Selangor. The face-to-face interview collected the demographic data included the age, gender, race, marital status, educational level, occupation, and history of fall. Then, the participants rated about their vision based on question given, “How is your eyesight (with glasses or contacts) if you wear them?” either “Excellent”, “Good”, “Fair”, “Poor”, or “Unable to see”. The visual acuity measurement was done with habitual or correction using LogMAR chart at 6 meters. RESULTS: The prevalence of VI among adults in urban populations of Shah Alam was 22.5%. Out of 40, they were 9 individuals reported “Fair” about their vision based on self-reported questionnaire. Female showed higher prevalence than the male. The highest prevalence of VI was reported among the age of 46-50 years old with prevalence of 7.5%. The area under the curve (AUC) of 1.000 in the ROC curve analysis indicated that the self reported was a good method to determine the VI over the visual acuity measurement. There was insignificant and poor association (p>0.05) (r<±0.30) between the demographic data with the visual impairment. CONCLUSIONS: The self-reported question can be suggested for quick, time-effective and save cost in determination of VI among adults.